Unusual formation and movement of a deep depression over Rajasthan during the monsoon season - VEERARAGHAVAN, K.; GHOSH, S. K. (MAUSAM, 1974)
An unusual formation arid intensification of a monsoon depression over Rajasthan is discussed. The upper air advection of positive vorticity in association with troughs in easterlies and westerlies on a pre-existing sea level system is found to be responsible for deepening. The uncommon southerly/south-eastern movement of the system is also explained.